1989
DOI: 10.1093/oxfordjournals.ndt.a091889
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Erythropoiesis in Dialysis Patients Receiving Recombinant Erythropoietin Treatment

Abstract: In eleven patients with uraemia on intermittent haemodialysis treatment, recombinant human erythropoietin (rHuEpo) was used at a dosage schedule of 100 IU/kg bodyweight thrice weekly. Erythrokinetic studies (blood volume, RBC survival and iron kinetics) were performed in nine cases before and after 6 months of treatment. The remaining two patients had only RBC and plasma volume determinations before and after treatment. Although total blood volume remained unchanged, RBC volume was increased in all cases. Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These seminal works and many subsequent studies sparked an interest in applying IEHH programs to increase erythrocyte mass as a way of improving the aerobic capacity of athletes. Recombinant human erythropoietin (rHuEPO) opened up a new chapter in the correction of uremic anemia due to chronic renal failure (Egrie et al, 1986 ; London et al, 1989 ; Najean et al, 1989 ), but also led to unethical use in sports medicine. The celebration of the 1968 Summer Olympics held in Mexico City (2,250 m above sea level) aroused interest in studying the effects of altitude on human performance.…”
Section: Biological Effects Of Intermittent Hypoxia Exposurementioning
confidence: 99%
“…These seminal works and many subsequent studies sparked an interest in applying IEHH programs to increase erythrocyte mass as a way of improving the aerobic capacity of athletes. Recombinant human erythropoietin (rHuEPO) opened up a new chapter in the correction of uremic anemia due to chronic renal failure (Egrie et al, 1986 ; London et al, 1989 ; Najean et al, 1989 ), but also led to unethical use in sports medicine. The celebration of the 1968 Summer Olympics held in Mexico City (2,250 m above sea level) aroused interest in studying the effects of altitude on human performance.…”
Section: Biological Effects Of Intermittent Hypoxia Exposurementioning
confidence: 99%
“…Erythropoietin therapy is useful in ameliorating renal anemia, which is generally accompanied by chronic renal failure. Two underlying mechanisms have been proposed to explain the effectiveness of erythropoietin in ameliorating renal anemia: one is that erythropoietin stimulates erythropoiesis and the other is that it extends the life span of erythrocytes [1,2].…”
Section: Dear Sirmentioning
confidence: 99%
“…Erythropoietin preparation produced by gene recombinant technique has been a well‐known contributor to the improvement of quality of life (QOL) in the patients since its introduction in the treatment of renal anemia. Many reports have already indicated that the improving effect of erythropoietin on renal anemia is attributable to its action to enhance hematopoietic function (1,2). However, there are also reports that erythropoietin administration could prolong the red blood cell life span that is reduced in hemodialysis patients (3,4,5).…”
Section: Introductionmentioning
confidence: 99%